Exploring English Teaching And Learning Writing Based On Scientific Approach At Eighth Grade - Ahmad Rifai Rifai; Siti Luruh Ayu Noerjanah (International Journal of Education and Humanities, 2021)
This research investigated the implementation of the scientific approach in English teaching and learning writing. This research aims to explore the implementation of a scientific approach and to identify the problems faced by the teachers and students related to the implementation of a scientific approach in English teaching and learning writing. In this research, the researcher used a descriptive qualitative method. The technique of collecting data was observation, interview, and documentation. The instrument of this research is the researcher herself. The results of the research show that the implementation of a scientific approach in English teaching and learning writing at eighth grade of SMPN 1 Karangsembung was well conducted by teachers but still not optimally. There are still many steps of activities that are often passed by teachers and the teachers still use the lecture method. Besides that, two factors faced by teachers in the implementation of scientific approach, internal and external factors. The internal factors include the teacher preparation in teaching such as still using the old method that was used in teaching. The external factors include the school preparation, such as the facilities provided by the school. Then, the problem faced by students is some students have low motivation in learning English. Therefore, they get difficulties mastering vocabulary. Moreover, the external factors in the teacher's strategy are not effective. It caused the students low enthusiasm and not interest in the learning process